Religiusitas dan Peer Attachment Terhadap Kebahagiaan pada Santri - Sugiyanto, Estia; Suwarti, Suwarti; Na’imah, Tri; Mildaeni, Itsna Nurrahma (Universitas Muhammadiyah Purwokerto, 2024)
The happiness of students in Islamic boarding schools is related to attachment, as students must be separated from their parents and adapt to a new environment. Additionally, students' religiosity, reflected through their religious activities, plays a crucial role. These two independent variables affect students' happiness in Islamic boarding schools. This study aims to examine the effect of religiosity and peer attachment on happiness among students at Darussalam Islamic Boarding School, Dukuhwaluh Purwokerto. The sample used in this study consists of 149 students. The research method employed is quantitative, using simple and multiple linear regression analyses with the assistance of SPSS for Windows version 26.00. The results indicate that religiosity significantly affects happiness, with an F-value of 72.184, a t-value of 8.496, and a significance (p) of 0.000 (p 0.05), with a determination coefficient (R-square) of 32.9%. The study also shows that peer attachment significantly affects happiness, with an F-value of 34.32, a t-value of 5.859, and a significance (p) of 0.000 (p 0.05), with a determination coefficient (R-square) of 18.9%. Furthermore, the results reveal that both religiosity and peer attachment together significantly affect happiness, with an F-value of 66.936, a t-value of 1.779, and a significance (p) of 0.000 (p 0.05), with a determination coefficient (R-square) of 47.8%. In conclusion, religiosity and peer attachment significantly affect students' happiness at Darussalam Islamic Boarding School.